2019
DOI: 10.2478/cjf-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Otolith Dimensions and Body Growth of North African Catfish Clarias gariepinus (Burchell, 1822) from the Upper Basin of the Sakarya River, Turkey

Abstract: The relationships between otolith size and body length of North African catfish Clarias gariepinus (Burchell, 1822), collected from Sakaryabaşı (the main spring area of the Sakarya River) between July 2014 and November 2014, were examined. Length-weight relationship was also calculated for overall specimens. The wild fish were captured by electrofishing using SAMUS 725MP. A total of 132 individuals ranging from 13.6 to 59.0 cm in total length and from 15.9 to 1755.0 g in weight were sampled. The lagenar otolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A strong relationship between fish length and otolith size suggests that somatic growth has a major effect on otolith growth (Munk 2012); there are published reports about similar relationships revealed between somatic and otolith growth (Aneesh-Kumar et al 2017;Yilmaz et al 2019). In the present study, linear regressions between fish length and otolith size showed a higher coefficient of determination (r 2 > 0.8) except between fish length and otolith height for L. bata.…”
Section: Discussionsupporting
confidence: 58%
“…A strong relationship between fish length and otolith size suggests that somatic growth has a major effect on otolith growth (Munk 2012); there are published reports about similar relationships revealed between somatic and otolith growth (Aneesh-Kumar et al 2017;Yilmaz et al 2019). In the present study, linear regressions between fish length and otolith size showed a higher coefficient of determination (r 2 > 0.8) except between fish length and otolith height for L. bata.…”
Section: Discussionsupporting
confidence: 58%
“…The studies on otolith biometry have focused on the relationship between fish length and otolith length (Granadeiro and Silva 2000;Viva et al 2015;Yılmaz et al 2019). Also, the relationships between fish length and different measurements (width, height) of otolith were frequently defined in recently (Yilmaz et al 2015;Aneesh Kumar et al 2017;Kanjuh et al 2018;Kurucu and Bostanci 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between otolith dimensions and fish length can be supply significant knowledge to determine fish length from otoliths in the stomach of predators and understand prey-predator relationships (Aguilar-Perera and Quijano-Puerto 2016). Although there have been a lot of studies on these relationships in many fish species (Viva et al 2015;Bostancı et al 2017;Yılmaz et al 2019), there are no known studies for Wels catfish.…”
Section: Introductionmentioning
confidence: 99%
“…Linear and nonlinear functions are preferred to describe relationships of otolith dimensions and fish size. Generally, the nonlinear function was used in otolith morphometrics and total length relationships (Waessle et al 2003;Saygin et al 2017;Jawad et al 2017;Kanjuh et al 2018;Zengin Özpiçak et al 2018;Yilmaz et al 2019;Saygin et al 2020;Bulatović et al 2021). However, in Ladik Lake, the linear regression model was found more stronger, and it was determined that the nonlinear regression is more useful in explaining the relationships between otolith measurements and total length.…”
Section: Otoliths Morphometrics and Total Length Relationshipsmentioning
confidence: 99%